Improving Student Learning Outcomes through Differentiated Learning and Adversity Intelligence - Hidayat, Nur; Ruhiyat, Yayat; Anriani, Nurul (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study aimed to determine the impact of differentiated Learning and Adversity Intelligence on the improvement of student learning outcomes. This investigation employs a quantitative approach and a 2x2 factorial design. The research sample comprised of 100 class X students out of SMKN 1 Keramat Watu’s total population of 200 students. The quantity of research samples was determined using the random sampling technique. Assessments of learning outcomes and adversity intelligence questionnaires are data collection instruments. Students are administered two types of assessments to acquire data. Fo = 7.911 and Sig = 0.005 0.05 indicated significant differences in the effect of differentiated learning on student learning outcomes with adversity intelligence. In addition, differentiated learning is more influential than CTL, as demonstrated by the scores, which ranged from 64.00 for a group of 30 students to 59.47 for a group of 20 students using differentiated learning and/or having low adversity intelligence. Differentiated learning allows students to investigate their unique abilities.